Performance evaluation of Free-Space-Optic (FSO) links - Alma, Husagic; Al-Khateeb, Wajdi Fawzi Mohammed (IIUM Press, 2011)
Once the knowledge about the basic performance parameters is gained it is possible to evaluate the performance of FSO links. Such is done firstly by evaluating all possible losses present in the channel, such as geometric, atmospheric and optical losses [1, 2]. Geometric losses are greatly dependent on the divergence angle and distance while atmospheric losses are created due to the signal's weakening due to atmospheric influence, or due to external performance factors mentioned earlier [3, 4]. Optical losses on the other hand are due to the physical configuration of each FSO terminal, and in some cases are negligible, as will be explained later in text. Knowing the losses or attenuation within the channel it is then possible to evaluate received power level and link margin, the main figures needed in order to evaluate the performance ofFSO links